Reducing Aggressive Behavior of Adolescent with Using the Aggression Replacement Training - Yulvi Hardoni; Meri Neherta; Rika Sarfika (Jurnal Endurance, 2019)
Adolescent is a transition period from childhood, therefore adolescents will show unique behavior and experience various difficulties in managing their emotions so that one of them will lead to aggressive behavior. Various impacts can occur due to aggressive behavior such as decreased learning achievement, bad social relations, anxiety, depression, and suicide. The goals of this study were to identify aggression replacement training can reduce aggressive behavior in adolescents. The design of this research is quasi experiment design and research design of one group pre-test post-test and sampling technique using purposive sampling. The population in this study were adolescents in vocational high school “X” in Padang city with a sample of 43 adolescents. Data were analyzed by using paired T-Test with significant value α=0,005. The results showed before giving aggression replacement training the average aggressive behavior of adolescents is 86.86 and after the average is 76.93. So it shows there is a significant difference in aggressive behavior between before and after given of aggression replacement training to adolescents. The influence aggression replacement training can reduce aggressive behavior in adolescents. The results of this study can be applied by psychiatric nurses for adolescents with aggressive behavior.